Pelaksanaan Supervisi Akademik Di MTs Yayasan Islam Rajamandala - Aryani, Asih; Nurjanah, Sya'adah Aisyah (Balai Diklat Keagamaan Surabaya, 2022)
The head of the madrasah as a supervisor in the education unit has a very important role in providing professional and accountable services to teachers, in particular providing motivation and support towards the development of a better learning process. The paradigm of teachers towards the implementation of supervision tends to be less good and many assume that supervision is an activity to supervise teachers in carrying out their learning by suppressing the freedom of teachers. The purpose of this study was to determine the implementation of academic supervision at MTs Islamic Foundation Rajamandala. The research method uses descriptive qualitative research and the analysis used is descriptive phenomenological. The results showed that the implementation of academic supervision in the planning aspect was still hampered by the presence of several teachers who had not completed the learning tools, in the aspect of the supervision implementation there were still some teachers who had not applied media and learning strategies/models, limited use of IT and authentic assessments that had not been able to fully implemented, while in the aspect of follow-up supervision, several teachers have been rewarded for their good performance by making them supervivors of colleagues and the Teacher Performance Assessment team. Keyword: Supervision, Principal, Teacher